EXTH-18. ENGINEERED EXOSOMES AS GENE DELIVERY TOOLS FOR THE TREATMENT OF GLIOBLASTOMA. (9th November 2020) - McDonald, Malcolm; Hossain, Anwar; Momin, Eric; Hasan, Irtiza; Singh, Sanjay; Adachi, Satoshi; Gumin, Joy; Ledbetter, Daniel; Daou, Marc; Gopakumar, Sricharan; Phillips, Lynette; Kerrigan, Brittany Parker; et al.
Abstract: Although we previously showed that exosomes are capable of delivering anti-glioma microRNAs (miRs) to brain tumors ( Lang et al. 2018 ), our studies revealed significant opportunity to 1) improve packaging and delivery efficiency of exosomes and 2) expand the repertoire of anti-glioma miRs. We hypothesized that incorporation of viral proteins into exosomes would enhance miR packaging and cell entry. To test this hypothesis, we engineered exosomes that express retroviral Gag and VSVg proteins (eExos). Specifically, HEK293T cells were transfected with Gag, VSVg, and with Cre-recombinase containing plasmid (pCre) to generate eExos-pCre. After 48hrs eExos-pCre were isolated by differential ultracentrifugation. Western analyses verified Gag and VSVg in eExos-pCre, and PCR documented pCre in these exosomes. Next, U87 cells harboring a dsRed-eGFP-loxP reporter-gene were treated with eExos-pCre or control exosomes. Flow cytometry demonstrated that eExos-pCre resulted in 82% conversion of red cells to green, compared with controls (2% conversion), verifying the effectiveness of eExos to deliver plasmids containing anti-glioma agents. To identify effective anti-glioma miRs, we conducted a high-throughput screen of 539 miRs against 7 glioma stem cell lines (GSCs) and identified miR-124-2, miR-135-a-2, and Let7i as the most potent anti-glioma miRs. We then studied the ability of eExos to package and deliver plasmids of these miRs either singly (eExos-miR-124, eExos-miR-135, eExos-miRLet7i) or as a tri-cistronic plasmid (eExos-miR-124-135-Let7i). Although eExos-miR-124, eExos-miR-135, and eExos-miRLet7i significantly decreased in vitro proliferation in all three GSCs (p< 0.01), eExos-miR-124-135-Let7i were most effective (p< 0.001). In in vivo studies, mice harboring GSC231 gliomas were injected with each of the eExos-miRs. Most significant improvement in survival was seen with eExos-miR-124-135-Let7i (median 75 versus 32.5 days for controls, p< 0.001). We conclude that eExos are a novel delivery strategy for human gliomas and that a tri-cistronic plasmid of miR-124-135-Let7i is highly effective against GBM and worthy of clinical translation.